Malignant spinal cord compression - Rajer, Mirjana (Radiology and oncology (Ljubljana), 2008)
Malignant spinal cord compression (MSCC) is a common and debilitating neurological complication of cancer. Because of the rapid progression of the neurological dysfunction, it is considered a medical emergency that demands a prompt diagnosis and treatment. Almost all of the MSCC are caused by an epidural compression from a tumour or a bony fragment from the collapsed vertebra affected by the metastasis. The most common of the tumours that metastasize to the spinal cord are breast and lung cancer, followed by lymphoma, myeloma, prostate cancer and sarcoma. Conclusions. The most common symptom of MSCC is pain, followed by muscular weakness and autonomic dysfunction. MRI provides the best information regarding MSCC, so all patientsshould have a MRI as soon as possible. If the MRI is contraindicated, patients should have the CT scan done. All patients with newly diagnosed MSCC should receive corticosteroids immediately, even before the definitive diagnosis is made. Other treatment options are surgery with postoperative radiotherapy, radiotherapy only, specific medical therapies according to the tumour type and symptomatic therapy, (mainly opiates). The decision of treatment modalities should be made according to the NOMS (neurological, oncological, mechanical and systemic) principles. In spite of the advances, the treatment is still palliative and many patients with MSCC have a poor prognosis and a short survival.
Keywords: hrbtenica; metastaze; rak (medicina); therapy; vtesnitev hrbtenjače; zdravljenje